2018
DOI: 10.1088/1361-6560/aaaca4
|View full text |Cite
|
Sign up to set email alerts
|

MRI-only treatment planning: benefits and challenges

Abstract: Over the past decade, the application of magnetic resonance imaging (MRI) has increased, and there is growing evidence to suggest that improvements in the accuracy of target delineation in MRI-guided radiation therapy may improve clinical outcomes in a variety of cancer types. However, some considerations should be recognized including patient motion during image acquisition and geometric accuracy of images. Moreover, MR-compatible immobilization devices need to be used when acquiring images in the treatment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
189
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(191 citation statements)
references
References 150 publications
(246 reference statements)
2
189
0
Order By: Relevance
“…Heterogeneity correction is required for accurate dose calculations, since bulk assignment of the whole body to water density can lead to large dosimetric errors for the head and neck region . To overcome the lack of electron densities on MRI, a so‐called pseudo‐CT or synthetic CT needs to be generated . Several methods have been proposed in literature to produce a synthetic computed tomography (sCT).…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneity correction is required for accurate dose calculations, since bulk assignment of the whole body to water density can lead to large dosimetric errors for the head and neck region . To overcome the lack of electron densities on MRI, a so‐called pseudo‐CT or synthetic CT needs to be generated . Several methods have been proposed in literature to produce a synthetic computed tomography (sCT).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, magnetic resonance imaging (MRI), as a structural imaging modality, offers improved soft‐tissue contrast and organ visualization compared to CT images. Beside excellent soft‐tissue contrast, advantages of MRI‐guided radiation therapy (RT) planning include no exposure to ionizing radiation and cost reduction as no planning CT needs to be acquired, multi‐parametric imaging possibilities offered by MRI, and elimination of uncertainties raised by imperfect coregistration . The fact that MRI does not directly provide electron density information owing to different physical principles, challenges the calculation of dose distribution based on MRI and is, aside from engineering aspects, one of the major limitations of combining an MR scanner with a linear accelerator …”
Section: Introductionmentioning
confidence: 99%
“…To streamline the workflow by implementing MRI alone in the planning process, several methods have been proposed for generating synthetic CT from MRI in various body sites. These methods have been reviewed comprehensively by Edmund and Nyholm, Johnstone et al, and Owrangi et al…”
Section: Introductionmentioning
confidence: 99%
“…To streamline the workflow by implementing MRI alone in the planning process, several methods have been proposed for generating synthetic CT from MRI in various body sites. These methods have been reviewed comprehensively by Edmund and Nyholm, 1 Johnstone et al, 2 and Owrangi et al 3 Previous studies have shown promising results in terms of synthetic CT quality, and demonstrated the potential of using MRI alone in the workflow for head [4][5][6][7][8][9][10] and pelvis [11][12][13][14][15] radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation